Synthesis of fluorinated SnO2 3D hierarchical structures assembled from nanosheets and their enhanced photocatalytic activity. Issue 107 (16th October 2015) - Wang, Youzhi; Cheng, Guoe; Zhang, Yu; Ke, Hanzhong; Zhu, Chunling
Abstract : Fluorinated 3D SnO2 hierarchical structures assembled from nanosheets were synthesized via a hydrothermal treatment and present excellent photocatalytic degradation of RhB. Abstract : Fluorinated SnO2 3D hierarchical structures assembled from nanosheets were synthesized via hydrothermal treatment of stannous fluoride in the presence of an appropriate amount of adipic acid. The as-prepared products were characterized in detail by FESEM/TEM/XRD/BET/XPS/UV-vis DRS techniques. The SnO2 nanosheets with tetragonal rutile structure were single-crystalline in nature and the exposed planes should be 11̄1 facets. A small amount of fluorine ions was observed to be adsorbed on the surface of SnO2 physically. It was found that both of F − and adipic acid played important roles in the formation of SnO2 nanostructures. The as-prepared product presented excellent photocatalytic degradation of RhB which reached 100% within 20 min under UV light irradiation.